I'm sorry...love, your husband eaudiobook Honest, hilarious stories from a father of three who made all the mistakes (and made up for them). - Edwards, Clint (Tantor Media, 2018)
Marriage and Kids are No Joke He may not win Father of the Year, but Clint Edwards has won the hearts of thousands—including the New York Times , Scary Mommy , and Good Morning America —thanks to his candor and irreverence when it comes to raising kids, being married, and learning from his mistakes. Clint has three children: Tristan (the know it all), Norah (the snarky princess), and Aspen (the worst roommate ever). He describes parenting as "a million different gears turning in a million different directions, all of them covered in sour milk." In this inspiring and unconventional book of essays, he sheds light on the darker yet hilarious side of domestic life. Owning up to all his mishaps and dumbassery, Edwards shares essays on just about every topic fellow spouses and parents can appreciate, including: stupid things he's said to his pregnant wife, the trauma of taking a toddler shopping, revelations on buying a minivan, and the struggle to not fight the nosy neighbor (who is five years old). Clint's funny, heartwarming account of the terrifying yet completely rewarding life of a parent is a breath of fresh air. Each essay in I'm Sorry . . . Love, Your Husband will have you thinking finally, someone gets it.